2018
DOI: 10.1101/339325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of the stress hormone cortisol on the metatranscriptome of the oral microbiome

Abstract: 15

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…[109][110][111] It was recently suggested that oral microorganisms can directly respond to the presence of stress hormones, a field termed "microbial endocrinology". 112 gression. 10,113 Further studies aimed at understanding the effects of stress on the oral microbiome are warranted.…”
Section: Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…[109][110][111] It was recently suggested that oral microorganisms can directly respond to the presence of stress hormones, a field termed "microbial endocrinology". 112 gression. 10,113 Further studies aimed at understanding the effects of stress on the oral microbiome are warranted.…”
Section: Stressmentioning
confidence: 99%
“…In the late 1990s, reports identified that stress associated with financial strain and inadequate coping behaviors was significantly associated with increased severity of periodontal disease 109‐111 . It was recently suggested that oral microorganisms can directly respond to the presence of stress hormones, a field termed “microbial endocrinology” 112 . Recent functional analysis of the effect of the stress‐related hormone cortisol on oral microorganisms (metatranscriptomics) identified that members of the phylum Fusobacteria become more active in the presence of cortisol 112 .…”
Section: Pregnancymentioning
confidence: 99%
“…Accordingly, the impact of cortisol on the community-wide transcriptome of the oral microbiome has been recently investigated and shifts in the gene expression profiles of the oral microbiota have been reported in a similar manner to those observed in vivo during periodontitis. 99 The authors found that pure cultures of F.…”
Section: Psycholog I C Al S Tre Ss and Periodontal Microb Iomementioning
confidence: 99%
“…Indeed, a significant enhancement for P. micra growth and an inhibitory effect for A. actinomycetemcomitans and some bacteria of the red and orange complexes were described [ 18 , 52 ]. A recent study based on a metatranscriptomic approach showed that glucocorticoids can directly induce changes in gene expression profiles of the oral microbiome, similar to those observed in periodontitis patients [ 53 ]. Moreover, patients suffering from periodontitis with a high-stress level exhibited a significant correlation between cortisol levels and T. forsythia detection compared to patients with low-stress levels or stress-managed patients.…”
Section: Discussionmentioning
confidence: 94%